2017
DOI: 10.1080/19491034.2017.1342915
|View full text |Cite|
|
Sign up to set email alerts
|

A demethylation deficient isoform of the lysine demethylase KDM2A interacts with pericentromeric heterochromatin in an HP1a-dependent manner

Abstract: Histone modifications have a profound impact on the chromatin structure and gene expression and their correct establishment and recognition is essential for correct cell functioning. Malfunction of histone modifying proteins is associated with developmental defects and diseases and detailed characterization of these proteins is therefore very important. The lysine specific demethylase KDM2A is a CpG island binding protein that has been studied predominantly for its ability to regulate CpG island-associated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
(93 reference statements)
0
17
0
Order By: Relevance
“…KDM2A/B-SF are thus likely to compete with KDM2A/B-LF or to complement their function (1). Despite the fact that a KDM2A-SF specific knockout mutant has not been described yet and it cannot be compared to the embryonically lethal KDM2A-LF knockout phenotype (24), we previously showed that the distinct KDM2A positive nuclear structures on pericentromeric heterochromatin are formed by KDM2A-SF and not by KDM2A-LF (12). Similarly, the fact that the KDM2B-SF specific knockout phenotype is different from that of the KDM2B-LF loss-of-function mutants also implies different functions for the short and long isoforms (25)(26)(27)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KDM2A/B-SF are thus likely to compete with KDM2A/B-LF or to complement their function (1). Despite the fact that a KDM2A-SF specific knockout mutant has not been described yet and it cannot be compared to the embryonically lethal KDM2A-LF knockout phenotype (24), we previously showed that the distinct KDM2A positive nuclear structures on pericentromeric heterochromatin are formed by KDM2A-SF and not by KDM2A-LF (12). Similarly, the fact that the KDM2B-SF specific knockout phenotype is different from that of the KDM2B-LF loss-of-function mutants also implies different functions for the short and long isoforms (25)(26)(27)).…”
Section: Introductionmentioning
confidence: 99%
“…Although KDM2A and KDM2B have very similar 3 structure, they have been shown to interact with different protein partners to repress different target regions. For example, KDM2A interacts with HP1a to repress the pericentromeric heterochromatin (11)(12)(13), whereas KDM2B forms complex with the PRC1 complex to silence developmentally important genes in embryonic stem cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Through the methylation of different histone sites, gene expressions can be regulated by influencing the activation and inhibition of transcription [5]. The constant level of covalent histone methylation is under the control of histone methyltransferases and demethylases [6]. The lysine-specific demethylase 2A gene (KDM2A), found on chromosome 11q13.2, is a member of the KDM histone lysine demethylase family, which exhibits specificity for removal of methyl groups of histone H3K36 by binding directly to CpG islands in gene promoters [6].…”
Section: Introductionmentioning
confidence: 99%
“…The constant level of covalent histone methylation is under the control of histone methyltransferases and demethylases [6]. The lysine-specific demethylase 2A gene (KDM2A), found on chromosome 11q13.2, is a member of the KDM histone lysine demethylase family, which exhibits specificity for removal of methyl groups of histone H3K36 by binding directly to CpG islands in gene promoters [6]. The dysfunction of KDM2A has been reported in various cancers, and its loss-of-function mouse mutants are embryonically lethal [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation